Substrate Rigidity Effect on CAD/CAM Restorations at Different Thicknesses - Pucci, César Rogério [UNESP] (2022)
Objectives  This article evaluated the effect of substrates rigidities on the post-fatigue fracture resistance of adhesively cemented simplified restorations in lithium disilicate glass ceramic. Methods  Precrystalized computer-aided design/computer-aided manufacturing ceramic blocks were processed into disc-shaped specimens (n = 10, O = 10 mm), mimicking a simplified restoration at two thicknesses (0.5 and 1.0 mm). Thereafter, the discs were cemented onto different base substrates (dentin analogue [control], dentin analogue with a central core build-up of resin composite [RC], or glass ionomer cement [GIC]). The specimens were subjected to mechanical cycling in a chewing simulator (100 N, 1 × 10 6cycles, 4 Hz) and then subjected to thermocycling aging (10,000 cycles, 5/37/55°C, 30 seconds). After the fatigue protocol, the specimens were loaded until failure (N) in a universal testing machine. Finite element analysis calculated the first principal stress at the center of the adhesive interface. Results  The results showed that restoration thickness, type of substrate, and their interaction were statistically significant (one-way analysis of variance; p < 0.001). Regardless the restoration thickness a higher fracture load was observed for specimens cemented to dentin analogue. Among the base materials, RC build-up presented the highest fracture load and lower stress magnitude for both restoration thicknesses in comparison with GIC build-up. The 0.5-mm restoration showed higher stress peak and lower fracture load when submitted to the compressive test. Conclusion  More flexible base material reduces the fracture load and increases the stress magnitude of adhesively cemented lithium disilicate restorations regardless the ceramic thickness. Therefore, more rigid substrates are suggested to be used to prevent restoration mechanical failures.